1974
DOI: 10.2307/1934427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity on Growth of Several Aquatic Macrophytes

Abstract: PURPOSE: The research reported herein investigated the effects of a range of lime (as calcium hydroxide; Ca(OH) 2) dosage levels on the growth of Sago pondweed in outdoor experimental mesocosms. BACKGROUND: Lime (CaCO 3 and Ca(OH) 2) application has been used primarily as a lake rehabilitation technique for limiting algal growth by controlling phosphorus availability in the water column and its release from the sediment (Prepas et al. 1990). At supersaturated concentrations, calcium co-precipitates with phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
3
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(81 citation statements)
references
References 8 publications
9
68
3
1
Order By: Relevance
“…These symptoms are similar to those described by Haller et al (1974) in a study conducted on the effect of salinity on growth of aquatic macrophytes. Haller et al (1974) reported toxic effects in water lettuce and water hyacinth when these plants were exposed to diluted seawater with salt concentrations of 1660 and 2500 mg/kg, respectively.…”
Section: Visual Observationssupporting
confidence: 88%
See 2 more Smart Citations
“…These symptoms are similar to those described by Haller et al (1974) in a study conducted on the effect of salinity on growth of aquatic macrophytes. Haller et al (1974) reported toxic effects in water lettuce and water hyacinth when these plants were exposed to diluted seawater with salt concentrations of 1660 and 2500 mg/kg, respectively.…”
Section: Visual Observationssupporting
confidence: 88%
“…These symptoms are similar to those described by Haller et al (1974) in a study conducted on the effect of salinity on growth of aquatic macrophytes. Haller et al (1974) reported toxic effects in water lettuce and water hyacinth when these plants were exposed to diluted seawater with salt concentrations of 1660 and 2500 mg/kg, respectively. Since a common measure of salinity is EC, an EC level was estimated for these figures using a conversion factor of 1000 mg/kg = 1616 S/cm, calculated from values given by Haller et al (1974).…”
Section: Visual Observationssupporting
confidence: 88%
See 1 more Smart Citation
“…From 2007 to 2009, biweekly to monthly water quality data were available for several additional locations around Susquehanna Flats, including inside the SAV bed and down-bay from the SAV bed. Salinity was not included in this analysis because values in and around the plant bed were generally , 1.0, well within the tolerance range of the dominant submersed plant species populating the study site (Haller et al 1974). Susquehanna River flow rates were measured at gauging stations located at Conowingo Dam (1968 to present) and at Harrisburg, Pennsylvania (1890 to present).…”
Section: Methodsmentioning
confidence: 99%
“…Other species may be more readily constrained by salinity. The aquatic plants E. densa and E. crassipes are limited to the mostly freshwater region east of Browns Island (Haller et al 1974;Hauenstein and Ramirez 1986). …”
Section: Salinitymentioning
confidence: 99%